Urgensi Perlindungan Hukum Terhadap Perempuan Dan Anak Korban Kekerasan - putu Sekarwangi Saraswati (Jurnal Ilmiah Raad Kertha, 2020)
Women and children as marginalized people whose existence in Indonesia are many objects of oppression because patrilineal culture makes women and children in Indonesia must be protected specifically in order to get definite and fair legal protection especially to women and children victims of violence, so that not many Indonesian women feel his life is always oppressed and not many children in Indonesia lose their future